3D Growth of Intragranular Pearlite in an Aged 100Mn13 Steel. Issue 11 (29th July 2021) - Liang, Bo; Ding, Zhimin; Xu, Zhenfeng; Yan, Feng; Tian, Rujin; Chen, Chen
Abstract : The morphology and microstructure of intragranular pearlite in 100Mn13 high‐carbon, high‐manganese steel aged at 600 °C are observed by a scanning electron microscope (SEM) and transmission electron microscope (TEM) and analyzed, and growth models describing the morphology and growth process in 3D space are proposed. The results show that pearlite could nucleate directly in the austenite grain and present a 3D morphology after deep etching, and ferrite and cementite in pearlite keep the orientation relationship (OR) with austenite, ( 2 2 ¯ 0 ) γ // ( 10 4 ¯ ) M 3 C, ( 1 ¯ 1 1 ¯ ) γ // ( 01 1 ¯ ) α, ( 0 1 ¯ 1 ¯ ) α // ( 1 ¯ 1 2 ¯ ) M 3 C, and [ 110 ] γ // [ 100 ] α // [ 461 ] M 3 C . Also, the overall continuous ledges at the lamellar ferrite surface and end surround the whole ferrite lamellae, corresponding to a fringe structure and a curved frontier interface in 2D space, which shows a terraced morphology in 3D space. The different structures of the α/γ interface in 3D directions result in different growth rates of ferrite lamellae, that is, edgewise grows fastest along the direction of [ 01 1 ¯ ] α due to the incoherent interface composed of ( 0 1 ¯ 1 ¯ ) α / / ( 1 2 ¯ 1 ¯ ) γ with a 28% mismatch, and sidewise grows slowest along the direction of [ 0 1 ¯ 1 ¯ ] α due to the coherent interface composed of ( 01 1 ¯ ) α / / ( 1 1 ¯ 1 ) γ with a 1.9% mismatch. Abstract : Lamellar pearlite nucleated directly in austenite grain displays a 3D terraced morphology, formed by the layer upon layer of ledges. Ferrite and cementite in intragranular pearlite keep orientation relationship with austenite, especially a new orientation relationship between cementite and austenite. Growth models describing the morphology and growth process of intragranular pearlite in 3D space are proposed.